2017
DOI: 10.3892/etm.2017.4778
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 inhibition by triptolide prevents inflammation in a mouse model of ulcerative colitis

Abstract: Abstract. The present study aimed to assess interleukin (IL)-6 expression in a murine model of ulcerative colitis (UC) induced by dextran sulfate sodium (DSS) and its potential association with the anti-colitis effects of triptolide (TL). Serum IL-6 levels were measured by ELISA. IL-6 gene expression levels in colonic mucosa specimens were assessed by reverse-transcription quantitative PCR and protein expression was evaluated by western blot analysis and immunohistochemistry. The expression of IL-6 was weak in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…Pharmacological and clinical tests have demonstrated its immunosuppressive, antiinflammatory, and other biological activities (Banerjee et al, 2013;Lin et al, 2001;Wu et al, 2013;Zheng et al, 2013). Triptolide exerts positive effects on UC (Wei et al, 2008;Zhang and Chen, 2017). Here, we used a DSS-induced UC mouse model and recorded general signs, DAI, and colon length, thickness, lesion gross score, and histopathology score along with the analysis of serum levels of TNF-a, IL-6, and IL-17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological and clinical tests have demonstrated its immunosuppressive, antiinflammatory, and other biological activities (Banerjee et al, 2013;Lin et al, 2001;Wu et al, 2013;Zheng et al, 2013). Triptolide exerts positive effects on UC (Wei et al, 2008;Zhang and Chen, 2017). Here, we used a DSS-induced UC mouse model and recorded general signs, DAI, and colon length, thickness, lesion gross score, and histopathology score along with the analysis of serum levels of TNF-a, IL-6, and IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts anti-inflammatory, immunosuppressive, and antitumor activities and has been widely used for the treatment of various inflammatory diseases (Lin et al, 2001;Lee et al, 2012;Wu et al, 2013;Zheng et al, 2013;Banerjee et al, 2013). Recent studies have shown that triptolide exerts beneficial effects against UC (Wei et al, 2008;Zhang et al, 2016;Zhang and Chen, 2017). Triptolide is also closely related to the gut microbiota through its immunosuppressive effects (Goldszmid and Trinchieri, 2012;Furusawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…40 IL-6 is an interleukin that acts as both a proinflammatory cytokine and an anti-inflammatory cytokine. 41 It is secreted by T cells and macrophages that can stimulate the immune response, thus causing inflammation if overexpressed. NO is a signaling molecule that plays a key role in the pathogenesis of inflammation.…”
Section: Intestinal Permeabilitymentioning
confidence: 99%
“…TrkB-PLC/IP3 pathway is mainly consisted of protein-tyrosine kinase receptor B (TrkB), phospholipase C (PLC) and inositol triphosphate (IP3). After the specific binding of brain-derived neurotrophic factor (BDNF) to TrkB, TrkB is phosphorylated to p-TrkB, which activates the signal transduction of PLC/IP3 in the downstream, thereby playing roles in the increase of intracellular Ca 2+ concentration, the enhancement of nerve-muscle excitation conduction, the promotion of cell mobility in the intestinal smooth muscle, and the promotion of intestinal motility [14][15][16][17][18][19]. At present, there is no research showing the regulatory mechanism of TrkB-PLC/IP3 pathway on colitis.…”
Section: Introductionmentioning
confidence: 99%